Beyond nature: The roles of visual appeal and individual differences in perceived restorative potential. (October 2019) - Twedt, Elyssa; Rainey, Reuben M.; Proffitt, Dennis R.
Abstract: Natural environments are typically judged to be more restorative than built environments in terms of fostering recovery from stress or buffering against resource depletion. But this comparison tends to be categorical – nature versus built environments – and consequently, questions remain regarding the restorative potential of environments that do not fit into these categories. Furthermore, individual differences in evaluations of perceived restorative potential is not well understood. In Study 1, participants rated the perceived restorative potential of environments that ranged on a continuum from natural to built. Environmental attributes and individual differences were measured to predict perceived restorative potential. In Study 2, we measured the relationship between self-reported need-for-restoration and perceived restorative potential. The results support an account of perceived restorative potential that emphasizes the importance of visual appeal, naturalness, and an absence of people as important environment dimensions. These factors are influenced very little by assessed individual differences other than perceived need-for-restoration. Highlights: A multi-level model to predict perceived restorative potential of places is proposed. Places varied continuously on dimensions of naturalness and visual appeal. Naturalness, visual appeal, and presence of people related to perceived restorative potential. Perceived restorative potential judgments were generally consistent, despite trait-level and socio-demographic variability. Need-for-restoration moderated preferences for built, mixed built-natural, and natural environments.